THE CALCULATION OF RATIONAL DESIGN AND TECHNOLOGY TRANSPORT SYSTEM USING SIMULATION MODELING - Олег, М. (Science-based technologies, 2012)
On the example of the features of Tecnomatix Plant Simulation examined the principles of simulation of air transportation systems. In the article indicated the place of simulation in the economic and technical analysis of business processes.